Image Content Indicators of Extremist Group Evolution: A Comparative Study of MENA-Based and Far-Right Groups - McMinimy, Kayla (Terrorism and political violence, 2025)
Policymakers, researchers, and responders alike focus on the evolution of terrorist and other groups associated with political violence. This study offers a comparative analysis of the images of ISIS and U.S. far-right groups’ use of flag images, as such emblems contribute to community building, heighten emotional responses, and have political import. It adds to previous work by comparing groups across the ideological spectrum, by recognizing differences in media operations present as groups evolve, and by focusing on visual messaging that is vital for influence in the online environment. Using chi-square analyses, it compares almost 5000 images that include flags from ISIS publications between 2014 and 2020 with 600 images focused on the far-right events at the Unite the Right Rally and the January 6 attack on the U.S. Capitol. Specifically, it looks at the compositional elements of the flags appearing in the images, the immediate media context within the photographic frame, and the broader regulatory, political, religious, and economic situational contexts. The findings indicate that while the far right and ISIS both heavily rely on flags in their visual images, eight key differences emerge as related to the groups, their contexts, and the evolution of the media systems.